Acquired resistance to EGFR‐targeted therapies in colorectal cancer. Issue 6 (14th May 2014) - Van Emburgh, Beth O.; Sartore-Bianchi, Andrea; Di Nicolantonio, Federica; Siena, Salvatore; Bardelli, Alberto
Abstract : Cetuximab and panitumumab are anti‐epidermal growth factor receptor (anti‐EGFR) monoclonal antibodies used as therapies for metastatic colorectal cancer patients. Intrinsic mechanisms of resistance, such as RAS mutations, can prevent patients from having a response with clinical benefit. The clinical efficacy of EGFR targeted antibodies is limited by the development of acquired (secondary) resistance, which typically occurs within 3–12 months from the start of therapy. Preclinical models and analyses of clinical samples have uncovered some of the alterations that confer a selective advantage to tumor cells when under the pressure of anti‐EGFR therapy. Molecular profiling of clinical specimens confirmed that genetic alterations of genes in the EGFR‐RAS‐RAF‐MEK signaling pathway and of receptor tyrosine kinases are mechanisms of acquired resistance to anti‐EGFR antibodies. The escape from anti‐EGFR blockade appears to converge on the (re)activation of MEK‐ERK or AKT as revealed in preclinical studies. Circulating tumor DNA and patient derived xenografts have proven useful tools to monitor patients for resistance to anti‐EGFR therapy and test combination therapies to overcome or reverse resistance. Highlights: Metastatic colorectal cancer patients can acquire resistance to anti‐EGFR therapy. Acquired resistance is driven by alterations in the EGFR‐RAS‐MEK pathway. Resistance mechanisms converge at activation of MEK‐ERK or AKT.